Relationship between Climatic Parameters and the Occurrence of Malaria and Measles in Urban Katsina, Katsina State, Nigeria - S. Dahiru; I.B. Abaje; O.F. Ati (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
This paper examines the relationship between some climatic parameters and the occurrence of malaria and measles in Urban Katsina in Katsina State, Nigeria. Climatic data (2012-2022) were obtained from archived of the Nigerian Meteorological Agency (NiMet), Umar Musa Yar’adua Airport, Katsina, while data on malaria and measles were obtained from the General Hospital Katsina and Federal Medical Center (FMC) Katsina ranging from 2012-2022. Pearson’s product-moment correlation statistics determined the relationship between the climatic parameters (maximum and minimum temperature, rainfall, relative humidity, and wind speed) and the selected diseases (malaria and measles). Findings revealed that climatic parameters influence the occurrence of both malaria and measles in urban Katsina. A low and negligible positive relationship exists between mean temperature and malaria in urban Katsina (r = 0.098, p= 0.774). Any increase in the mean temperature will lead to an increase in malaria incidence in the study area. Further findings revealed that any decline in the rainfall yield will decrease the spread of measles in the study area. The study concludes that climatic parameters influence the spread and occurrence of malaria and measles in urban Katsina. Spraying insecticide against mosquitoes and the use of mosquito nets at night is recommended, and all children should be vaccinated against measles.